2018
DOI: 10.1038/nm.4461
|View full text |Cite
|
Sign up to set email alerts
|

The deubiquitinating enzyme cylindromatosis mitigates nonalcoholic steatohepatitis

Abstract: Nonalcoholic steatohepatitis (NASH) is a common clinical condition that can lead to advanced liver diseases. Lack of effective pharmacotherapies for NASH is largely attributable to an incomplete understanding of its pathogenesis. The deubiquitinase cylindromatosis (CYLD) plays key roles in inflammation and cancer. Here we identified CYLD as a suppressor of NASH in mice and in monkeys. CYLD is progressively degraded upon interaction with the E3 ligase TRIM47 in proportion to NASH severity. We observed that over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
113
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 117 publications
(128 citation statements)
references
References 58 publications
7
113
0
Order By: Relevance
“…However, the overall experimental design for the cited studies 14,9 in this correspondence challenges the conventional doctrine of previous findings on pre-existing NABs against AAV virus. For example, in the above studies in question, it was not stated whether any of the monkeys were screened for AAV8 NABs.…”
Section: To the Editormentioning
confidence: 90%
See 3 more Smart Citations
“…However, the overall experimental design for the cited studies 14,9 in this correspondence challenges the conventional doctrine of previous findings on pre-existing NABs against AAV virus. For example, in the above studies in question, it was not stated whether any of the monkeys were screened for AAV8 NABs.…”
Section: To the Editormentioning
confidence: 90%
“…Recently, Hongliang Li and colleagues 14 published four studies in Nature Medicine applying AAV serotype 8 vectors (AAV8) in nonhuman primate (NHP) models of nonalcoholic steatohepatitis. In each study, genes delivered to the liver via AAV vectors demonstrated transduction in these large animal models, and therapeutic effects were achieved.…”
Section: To the Editormentioning
confidence: 99%
See 2 more Smart Citations
“…These MetS‐predisposed monkeys exhibit higher blood pressure and body weight than healthy controls. Importantly, moderate steatosis and inflammation developed in MetS‐predisposed monkeys fed a normal chow diet, and they also exhibit clear increases in the hepatic expression of profibrotic genes . When fed an HFD or even a simple high‐carbohydrate diet, MetS‐predisposed monkeys rapidly become obese and insulin resistant and develop hepatic inflammation with fibrosis .…”
mentioning
confidence: 99%